System simulation and exergetic evaluation of hybrid propulsion system for crude oil tanker: A hybrid of solid-oxide fuel cell and gas engine. (1st November 2020) - Giap, Van-Tien; Lee, Young Duk; Kim, Young Sang; Ahn, Kook Young; Kim, Dae Hee; Lee, Jung Il
Highlights: Two types of SOFC-gas engine hybrid propulsion system for crude oil tanker are proposed. The proposed hybrid concepts are indirect- and direct-coupling systems. Optimal configuration and operating condition are determined using system simulations. The indirect- and direct-coupling systems reduce CO2 emission by 9% and 16%, respectively. By the direct-coupling of SOFC and gas engines, the overall exergy destruction is reduced by 32%. Abstract: This study investigates a hybrid electrical propulsion system of gas engines and a solid-oxide fuel cell (SOFC), quantifying the CO2 emission and proposing a way to further reduce CO2 emissions. The indirect-coupling and direct-coupling configurations are proposed and analyzed from the perspectives of energy and exergy. In the indirect-coupling configuration, the engine and fuel cell system are only integrated electrically without the transfer of any heat or material stream. In the direct-coupling configuration, the unused remaining fuel, which is released from the fuel cell, is transported to the gas engine, and the unused surplus steam, which is produced from the engine exhaust, is provided with the reforming section of the fuel cell system. An Aframax-class crude oil tanker is selected as an application; detailed information of its operational mode is used to quantify the CO2 emission of crude oil delivery. Results reveal that the indirect-coupling hybrid system reduces CO2 emission by a maximum of 9% when a 5-MW SOFC system is integrated with 4.7-MW gas engines. For the direct-coupling configuration, a further reduction of 16% in CO2 emission is achieved. Results of the exergy analysis show that the gas engines and SOFC are the primary contributors to the exergy destruction, and contribute to thermodynamic inefficiencies. By implementing the direct-coupling configuration, the exergy destruction of the overall system can be reduced by 32% by utilizing the unused fuel and steam in a more effective way.